Akibat Hukum Yang Ditimbulkan Terhadap Perjanjian Keabsahan Hukum Pada Perjanjian Jual Beli Elektronik Yang dilakukan Anak dibawah Umur Menurut Hukum Kontrak dan Undang-Undang Nomor 19 Tahun 2016 Tentang Informasi dan Transaksi Elektronik - Aldan Syaifullah Alulu; Weny Almoravid Dungga; Zamroni Abdussamad (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to find out how the legal validity of electronic sales and purchase agreements made by minors is reviewed in contract law and Law Number 19 of 2016 concerning electronic information and transactions and what legal consequences arise from the legal validity of electronic sales and purchase agreements. What Minors Do According to Contract Law and Law Number 19 of 2016 concerning Information and Electronic Transactions. Normative legal research uses normative case studies in the form of legal behavioral products, for example reviewing laws. The subject of the study is law which is conceptualized as a norm or rule that applies in society and becomes a reference for everyone's behavior. So normative legal research focuses on positive law inventory, legal principles and doctrine, legal discovery in cases in concreto, legal systematics, synchronization level, legal comparison and legal history. The results of this research show that (1) Agreements in electronic transactions via electronic media made by minors are said to be invalid because they conflict with the conditions for the validity of agreements in the Civil Code and the Electronic Information and Transactions Law (2) The legal consequences of agreements in electronic transactions via electronic media for minors for legal settlement efforts can only be carried out through guardianship. If minors do not meet the subjective requirements, namely the ability to make an agreement, the agreement made can be cancelled.